Strengthening Collaborative Governance in Efforts to Reduce The Mortality Rate of Mother and Baby - Farida Nurani (Indonesian Association for Public Administration (IAPA), 2020)
This research aims to learn the role of each government agency and community involved in the policy program for reducing maternal and infant mortality rate in Jember district. Then hope to come up with recommendations for strengthening the role of stakeholders in an effort to realize good governance. Given that in 2012, Jember district was listed as the district with the highest IMR and MMR in East Java. One of the collaborative policy programs launched to reduce the high IMR and MMR in Jember Regency is the Copy of Decision of Jember Regent Number: 188.45 / 101.1 / 012/2015 About Perinatal Maternal Audit Team of Jember Regency Year 2015. The descriptive qualitative research method used (before the C19 pandemic) was in-depth interviews, three FGDs with stakeholders. Data analysis by Spreadly analysis (taxonomic analysis, component analysis and cultural themes). The results showed that the ego-centricity of each government institution was still very prominent, and community participation was still mobilizing. Thus, efforts to strengthen collaborative governance roles are needed through the role of leading actors who are strongly committed to directing, controlling and monitoring policy programs that have been made.